Efeito antimicrobiano e modulador da resposta imune dos peptídeos hBD-3 e LL-37 e dos polifenóis o chá verde e do cranberry - Bedran, Telma Blanca Lombardo [UNESP] (2014)
The antimicrobial peptides LL-37, hBD-1, hBD-2 and hBD-3 are considered an endogenous antibiotic, with important role in the prevention of periodontal diseases due to their ability to regulate the immune response. However those peptides could be degraded by periodontal pathogens. Therefore, therapies able to up regulate the secretion of those peptides by human cells, and the association of antimicrobial peptides with natural compounds, which may act in synergism to modulate the immune response, may be a novel approach for effectively controlling periodontal diseases. The aim of this in vitro study were: i) investigate the ability of green tea extract and EGCG to induce hBD-1 and hBD-2 secretion and gene expression by gingival epithelial cells (B11) and to protect hBDs from degradation by P. gingivalis, ii) A 3D co-culture model of gingival epithelial cells and fibroblasts stimulated with A. actinomycetemcomitans LPS (1 μg/ml) were used to investigated the anti-inflammatory properties of the hBD-3, LL-37, ACPACs and EGCG and to determine whether LL-37 acts in synergy with AC-PACs, EGCG and hBD-3. Gingival epithelial cells were stimulated with green tea extract or EGCG in the presence and absence of specific inhibitors. The secretion and gene expression of hBD-1 and hBD-2 was respectively measured by ELISA and qPCR. The ability of green tea extract and EGCG to prevent hBDs degradation by P. gingivalis present in a bacterial culture supernatant was evaluated by ELISA. A 3D co-culture model composed of gingival fibroblasts embedded in a collagen matrix overlaid with gingival epithelial cells had a synergistic effect with respect to the secretion of IL-6 and IL-8 in response to A. actinomycetemcomitans LPS stimulation compared to fibroblasts and epithelial cells individually. The 3D co-culture model was stimulated with noncytotoxic concentrations of: i) hBD-3 (10 and 20 μM) ...(Complete abstract electronic access below)